Alzheimer’s, Memory, Migration from Istria: Caterina Edward’s Finding Rosa - Concilio, Carmen (Italian Canadiana)

(untitled) (Iter Press, 2023)
Finding Rosa (2008) is a quest for the documentation that might prove the true identity, provenance, and date of birth of Caterina’s mother, Rosa. Diagnosed with Alzheimer’s disease, Rosa is slowly losing her mind and memory; therefore, it becomes even more urgent to know the truth about her early life in Istria. Istria’s international, complex history is unravelled in the novel, while a story of migration from that former Italian territory – first to England and finally to Canada – grows into a historical drama of forced removals, refugee camps, and diaspora for the majority of Italian Istrians, forced to abandon their abodes by the pressure of Tito’s Yugoslavia in 1947, the year of the so-called “Great exodus.” On the one hand, Ageing and Alzheimer’s Studies can help us understand Rosa’s medical condition, as well as the condition of Caterina in the role of caregiver, within the structure and drama of a memoir and a Familienroman; on the other hand, Historical and Border Studies are the methodological frameworks with which to look at Istria in this revealing historical novel.